Apakah Akun Media Sosial Berbasis Konten Pariwisata Menciptakan Keinginan Wisatawan untuk Mengunjungi Destinasi Wisata? - Olivia Barcelona Nasution (Telaah Bisnis, 2021)
Online tourism marketing is one of the most effective marketing efforts to do nowadays, especially in digital era. This study aims to examine the effect of source credibility and content quality on tourists perceived image and the effect of perceived image on the intention to visit tourism destinations. The research model was tested using data from questionnaires distributed online (n = 263) and using Structural Equation Modeling analysis. All hypotheses in this study are accepted and source credibility has the most influence on tourists’ the perceived image.